Financing resource recovery and reuse in developing and emerging economies: enabling environment, financing sources and cost recovery - Lazurko, Anita; Drechsel, Pay; Hanjra, Munir A. (International Water Management Institute, 2018)
Resource recovery and reuse (RRR) of domestic and agro-industrial waste has the potential to contribute to a number of financial, socioeconomic and environmental benefits. However, despite these benefits and an increasing political will, there remain significant barriers to build the required up-front capital which is discouraging private sector engagement. A systematic analysis and understanding of the enabling environment, public and private funding sources, risk-sharing mechanisms and pathways for cost recovery can help to identify opportunities to improve the viability of RRR solutions. This report looks at regulations and policies that remove disincentives for RRR, public and private funding sources for capital and operational costs, risk mitigation options through blending and structuring finance, and options for operational cost recovery.